Optimal design of the vehicle mechatronic ISD suspension system using the structure-immittance approach. (March 2022) - Shen, Yujie; Hua, Jie; Wu, Bin; Chen, Zhong; Xiong, Xiaoxia; Chen, Long
There are three types of two-terminal mechanical elements, namely the inerter, the spring, and the damper in the vehicle ISD suspension system, and how to design the suspension structure has drawn much attention in automotive engineering fields. Due to the advantage of using the external electrical network to simulate the corresponding mechanical impedance output, a ball-screw mechatronic inerter is adopted in the optimal design procedure in this paper. A half vehicle dynamic model considering the vehicle body vertical motion and pitch motion is established, and the optimal design methodology of the vehicle mechatronic ISD suspension is proposed by using the structure-immittance approach to ensure the simplicity of the suspension structures. The dynamic performance indexes constraints are taken into account, and the optimal structures are discussed in detail. Numerical simulations results show that, the dynamic performance indexes, namely the RMS (root-mean square) of the vehicle body vertical acceleration and the RMS of the pitch motion acceleration of the mechatronic ISD suspensions can be reduced by 31% and 35% without constraints, and 18% and 15% with constraints by comparing to the passive suspension system. The structure-immittance approach can be easily adopted in the vehicle suspension structural design, and the research fruits will provide a new thought for the application of the inerter element in automotive engineering.